1999
DOI: 10.1099/0022-1317-80-1-261
|View full text |Cite
|
Sign up to set email alerts
|

Novel endogenous retroviral sequences in the chicken genome closely related to HPRS-103 (subgroup J) avian leukosis virus.

Abstract: HPRS-103, the prototype of avian leukosis virus (ALV) subgroup J, is a recently identified retrovirus associated with myeloid leukosis in meat-type chickens. Although this virus shows high sequence identity to other ALV subgroups within the gag and pol genes, its env gene is highly diverged (with only about 40 % sequence identity) from other ALV subgroups. On the other hand, the sequence of the env gene of HPRS-103 was 75 % identical to that of E51, a member of the EAV family of endogenous avian retroviruses. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
38
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(41 citation statements)
references
References 22 publications
2
38
0
Order By: Relevance
“…After the first isolation of the ALV-J prototype virus, HPRS-103, more than 10 years ago in the United Kingdom (21), viruses belonging to this subgroup have spread rapidly to many countries, becoming one of the major pathogens facing the broiler meat industry worldwide (26). The env gene of ALV-J is closely related to that of a novel group of chicken endogenous retroviral elements designated EAV-HP (24), suggesting that ALV-J has emerged by genetic recombination (17). Compared to the pathogenic ALV subgroups, such as A and B, which primarily induce lymphoid leukosis in genetically susceptible birds (18), ALV-J isolates predominantly induce myeloid leukosis (ML), a property thought to be associated with their tropism for the cells of the myeloid lineage (1).…”
mentioning
confidence: 99%
“…After the first isolation of the ALV-J prototype virus, HPRS-103, more than 10 years ago in the United Kingdom (21), viruses belonging to this subgroup have spread rapidly to many countries, becoming one of the major pathogens facing the broiler meat industry worldwide (26). The env gene of ALV-J is closely related to that of a novel group of chicken endogenous retroviral elements designated EAV-HP (24), suggesting that ALV-J has emerged by genetic recombination (17). Compared to the pathogenic ALV subgroups, such as A and B, which primarily induce lymphoid leukosis in genetically susceptible birds (18), ALV-J isolates predominantly induce myeloid leukosis (ML), a property thought to be associated with their tropism for the cells of the myeloid lineage (1).…”
mentioning
confidence: 99%
“…The EAV-HP (also designated ev/J), the most recently identified members of the endogenous avian retrovirus (EAV) family, are present in Gallus species as 10 to 15 copies per genome (12). Four different structures of EAV-HP proviruses have been identified in the chicken genome.…”
mentioning
confidence: 99%
“…Because retroviral integration can be considered random, each ERV is present at a unique chromosomal location (Stoye, 2012). The overwhelming majority of ERVs have been identified using hybridization (Hayward and Hanafusa, 1975;Martin et al, 1981;Chambers et al, 1986;Smith et al, 1999) and polymerase chain reaction (PCR) strategies by amplifying conserved viral sequences (Smith et al, 1999;Xiao et al, 2008) in various animal species. Herniou et al (1998) identified ERVs in reptilian, amphibian, and piscine vertebrates using PCR to amply viral sequence-coding protease and reverse transcriptase.…”
Section: Introductionmentioning
confidence: 99%